The effect of antibiotic therapy on Salivary Catalase kinetic parameters in neonatal at risk of Sepsis - Ari Yunanto; Pricilia Gunawan Halim; Iskandar Iskandar; Eko Suhartono (Indonesian Journal of Perinatology, 2020)
Introduction: This study describes the effect of antibiotic therapy on salivary catalase kinetic parameters (CAT) at neonatal at risk of sepsis. Methods: Study is conducted from February – June 2015. Salivary samples are obtained from 20 neonates (5 normal-healthy neonates and 15 neonates at risk of sepsis) at Ulin General Hospital, Banjarmasin, Indonesia. The samples were placed in four different groups: P0 as control group (saliva + hydrogen peroxide/H2O2), P1 (saliva + 2 mg Ampicillin + H2O2), P2 (saliva + 0.2 mg Gentamicin + H2O2), P3 (saliva + 2 mg Ampicillin + 0.2 mg Gentamicin + H2O2). The solution is incubated at 37oC and 40oC before catalase (CAT) activity is measured. Catalase activity is measured by using a spectrophotometer at 240 nm. Kinetic parameters are measured at different concentrations of H2O2 and temperature. Kinetic parameters are represented by the Michaelis-Menten constant (Km) and the maximum reaction speed (Vmax) obtained through the Lineweaver-Burk curve plot. Results: The Km of Catalase on the saliva of neonates at risk of sepsis treated with antibiotics (4.37, 1.84, 0.12, and 0.23, 3.74, 1.5, for P1, P2, P3 respectively) was lower than the control group (17.61 and 12.54), both at 37ºC and 40ºC. Similarly, Vmax of the neonates at risk of sepsis treated with antibiotics (0.46, 0.34, 0.04 and 0.07, 0.20, 0.24) was lower than the control group (1.47 and 0.53) at 37ºC and 40ºC. Conclusion: The study shows that the Catalase activity at the saliva of newborns at risk of sepsis treated with antibiotic was lower than the control group.